New horizons in modulating the radio-sensitivity of head and neck cancer - 100 years after Warburg’ effect discovery - Mireștean, Camil Ciprian; Iancu, Roxana Irina; Iancu, Dragoș Petru Teodor (Frontiers in Oncology, 2022)
Tumor radiation resistance along with chemotherapy resistance is one of the main causes of therapeutic failure of radiotherapy-treated head and neck cancers. 100 years after the discovery of the Warburg effect, a process specific to malignant cells to metabolize glucose especially anaerobically even under normoxia condition, its modulation has become a viable therapeutic target for improving the results of cancer therapies. Improving the radio-sensitivity of head and neck tumors by reversing the Warburg effect can increase the rate of local control and reduce the toxicity associated with irradiation. P53 status can be used as a biomarker in the choice of a single agent strategy (cell respiration inhibition with Metformin) or double inhibition, both of respiration and glycolysis. Targeting of enzymes involved in the Warburg effect, such as Hexokinase-II, are strategies with potential to be applied in clinical practice with radio-sensitizing effect for head and neck squamous cell carcinoma. Even if anti-Warburg therapies tested in clinical trials have been associated with either toxic deaths or a minor clinical benefit, the identification of both potential radio-sensitivity biomarkers and methods of reversing the Warburg effect will play an important role in the radiobiology of head and neck cancers.